Safety of Pancreatic Resections in Octogenarians - Taffurelli, Giovanni; Ricci, Claudio; Lazzarini, Enrico; D’Ambra, Marielda; Buscemi, Salvatore; Pezzilli, Raffaele; Pacilio, Carlo Alberto; Monari, Francesco; Antonacci, Nicola; Casadei, Riccardo; et al. (JOP. Journal of the Pancreas, 2013)
Context The safety of pancreatic resections in very elderly patients is still controversial. Objective To evaluate postoperative mortality, morbidity, type of discharge and length of hospital stay (LOS) in octogenarians who underwent pancreatic resections for malignancy. Methods From 2004 to 2013, 213 patients underwent pancreatic resections and were recorded in a prospective data base. They were divided in three groups: <70 years, 70-80 years and ≥80 years and were analyzed regarding postoperative course. Multivariate analysis was carried out to verify the impact of age on postoperative results. Results Mortality rate was higher (P=0.029) in patients ≥80 years (16.7%) only when compared with patients <70 years (3.4%). Morbidity rate was similar in the three groups. The discharge home was more frequent in patients <70 years (94.6%) and in those 70-80 years (92.3%) respect on patients ≥80 years (55%; P<0.001). LOS was similar in patients <70 years and in those 70-80 years, while it results higher in those aged ≥80 years (P=0.021). At multivariate analysis, patients aged 70-80 and ≥80 years had an increased risk of postoperative mortality (OR=7.1, P=0.022 and OR=6.3, P=0.050, respectively) as well as malnourishment (OR=4.5, P=0.029). Age did not influence morbidity while ASA score 4 increased risk of complications (OR=7.0, P=0.018). Distal pancreatectomy (DP) or an atypical resection reduced the risk (OR=0.4, P=0.008 and OR=0.1, P=0.049, respectively) respect on major procedures. Discharge to health care facility was more frequent in patients ≥80 years (OR=74.5, P<0.001), with ASA score 4 (OR=48.9, P=0.023), comorbidities (OR=25.4, P=0.011) or jaundice (OR=119.2, P=0.004) and in those performing DP (OR=26.7, P=0.039). Biliary stenting reduced the odds to health care facility (OR=0.1, P=0.041). LOS was increased by comorbidities, chronic renal failure and jaundice by 25% (P=0.039), 64% (P=0.003) and 36% (P=0.010), respectively. Total pancreatectomy reduced LOS by 14% (P=0.036). Conclusions Age ≥80 years increased the risk of postoperative mortality and discharge to health care facility after pancreatic resections.